1983
DOI: 10.1111/j.1745-4557.1983.tb00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soy Particle Size and Color on the Sensory Properties of Ground Beef Patties

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
(7 reference statements)
1
6
0
1
Order By: Relevance
“…The data on tenderness of samples revealed that the patties were positively affected by TSP addition, i.e., the samples which TSP were considered more tender than the sample without TSP (control), by the panel. These findings support previous work by Cardello et al (1983) and Cross et al (1975). Liu et al (1991) reported that the addition of soy protein gave a more tender ground beef patty, however the juiciness of the products decreased with the addition of TSP.…”
Section: Sensory Evaluationsupporting
confidence: 91%
See 1 more Smart Citation
“…The data on tenderness of samples revealed that the patties were positively affected by TSP addition, i.e., the samples which TSP were considered more tender than the sample without TSP (control), by the panel. These findings support previous work by Cardello et al (1983) and Cross et al (1975). Liu et al (1991) reported that the addition of soy protein gave a more tender ground beef patty, however the juiciness of the products decreased with the addition of TSP.…”
Section: Sensory Evaluationsupporting
confidence: 91%
“…1988;McMindes 1991) and even other ingredients such as carrageen and oat meal (Desmond et al 1998;Egbert et al 1991;Giese 1992;Pszczola 1991;Taki 1991) on the quality of the products. Some studies showed the effects of soy protein extenders on the color of ground beef patties (Judge et al 1974;Smith et al 1976). Cardello et al (1983 pointed out the importance of investigating the visual properties of ground beef patties.…”
Section: Introductionmentioning
confidence: 99%
“…2) but appearance was not unacceptable. As noted by Cardello et al (1983), both color and particle size of protein ingredients affect visual and textural appearance of extended patties. The lowest appearance (5.4) and color (6.1) scores were observed for nuggets containing 20% FCF.…”
Section: Consumer Acceptabilitymentioning
confidence: 95%
“…The lowest appearance acceptability score (5.2) observed for nuggets containing 20% FCF may have been due to the particle size of FCF. As noted by Cardello et al (1983), both color and particle size of protein ingredients affect visual and textural appearance of extended beef patties. Although FCF particles were uniformly dispersed and suitably small to allow good binding of water, fat, and chicken pieces during nugget preparation, particles were large enough to be discernible at the surface and in the interior of nuggets.…”
Section: Indicate Thatmentioning
confidence: 95%